Electronic health records for better health in the lower- and middle-income countries: A landscape study. Issue 4 (9th March 2020) - Kumar, Manish; Mostafa, Javed
Abstract : Purpose: Electronic health records (EHR) can enable collection and use of data for achieving better health both at the patient and population health levels. The World Health Organization's (WHO) draft 2019 four-year global digital health strategy aims to "improve health for everyone, everywhere by accelerating the adoption of appropriate digital health" and EHRs are key to achieving better health goals. Despite the fact that EHRs can help to achieve better health, there is lack of evidence explaining national and sub-national EHR development in the limited resource settings. Design/methodology/approach: We conducted a landscape study to describe the EHR development and use in the low- and middle-income countries for achieving better health. We reviewed literature from four scientific databases and analyzed gray literature identified in consultation with 17 international experts. Findings: The findings of this literature review are presented in three subsections. The first two subsections describe key stakeholders for development of national and sub-national EHR and health information architecture which includes status of ehealth foundations, EHR, and sub-systems in the country. The third subsection presents and discusses key challenges related to sustainability of national and sub-national EHRs. The findings in these three subsections are further explored through examples of health information flow in Uganda, and electronic medical record/EHR implementation in Sierra Leone and Malawi. These examples briefly describe stakeholders, information architecture, and sustainability challenges. Originality/value: This paper fills an important research gap and clearly explains the urgent research need to build context-specific EHR development models to enable use of data for better health.